Antagonism and antifungal activity of Humphreya coffeata (Berk.) Steyaert against Rhizopus stolonifer (Ehrenb.) Vuill. - Téllez-Téllez, Maura; Amaro-Guadarrama, Benjamín; Agapito-Ocampo, Alma Rosa; Acosta-Urdapilleta, Ma. de Lourdes (Ecosistemas y Recursos Agropecuarios, 2024)
The fungus Rhizopus stolonifer causes the rotting of fruits and vegetables, so it is important to search for biological control alternatives. The objective was to perform antagonism and evaluate the antifungal activity of H. coffeata against R. stolonifer. The percentage reduction in mycelial growth (PRCM) and the type of antagonism of R. stolonifer were evaluated when growing it together with the antagonist strains, and the antifungal activity of the H. coffeata culture broth was evaluated. The PRCM was higher for H. coffeata and Daldinia sp.; they presented class 1 antagonism and contact inhibition since the mycelium of H. coffeatarolled up the hyphae of R. stolonifer. The three H. coffeata culture broths affected the growth of R. stolonifer, but it was more evident in the coculture, so through this system molecules can be obtained to be used in the bio-control of R. stolonifer.